Hydrogen sulfide is a novel potential virulence factor of Mycoplasma pneumoniae: characterization of the unusual cysteine desulfurase/desulfhydrase HapE. Issue 1 (9th February 2016) - Großhennig, Stephanie; Ischebeck, Till; Gibhardt, Johannes; Busse, Julia; Feussner, Ivo; Stülke, Jörg
Summary: Mycoplasma pneumoniae is a human pathogen causing atypical pneumonia with a minimalized and highly streamlined genome. So far, hydrogen peroxide production, cytadherence, and the ADP‐ribosylating CARDS toxin have been identified as pathogenicity determinants. We have studied haemolysis caused by M. pneumoniae, and discovered that hydrogen peroxide is responsible for the oxidation of heme, but not for lysis of erythrocytes. This feature could be attributed to hydrogen sulfide, a compound that has previously not been identified as virulence factor in lung pathogens. Indeed, we observed hydrogen sulfide production by M. pneumoniae . The search for a hydrogen sulfide‐producing enzyme identified HapE, a protein with similarity to cysteine desulfurases. In contrast to typical cysteine desulfurases, HapE is a bifunctional enzyme: it has both the cysteine desulfurase activity to produce alanine and the cysteine desulfhydrase activity to produce pyruvate and hydrogen sulfide. Experiments with purified HapE showed that the enzymatic activity of the protein is responsible for haemolysis, demonstrating that HapE is a novel potential virulence factor of M. pneumoniae . Abstract : Mycoplasma pneumoniae is a minimal human pathogen. Here, we demonstrate that the hydrogen sulfide produced by the bacterium from cysteine causes haemolysis. The hydrogen sulfide is generated by the novel bifunctional cysteine desulfurase/desulfhydrase HapE. Our findings suggest that HapE may be a novel virulence factor in M. pneumoniae .